Enhanced overloaded code division multiple access for network on chip - Behnam Vakili; Morteza Gholipour (IET Computers & Digital Techniques)
Abstract The Code‐division multiple access (CDMA) method is commonly used as the network infrastructure in multi‐core chips. One of its advantages is the simultaneous connection of all network components. Another advantage is the constant delay of this method. On the other hand, one drawback is that the number of transmitters is limited to the number of encoding bits. In this study, the authors used the combination of Walsh codes and their inverses, as well as the simultaneous application of the time‐division multiple access (TDMA) method, to increase the transmission capacity of this protocol more than four times the standard mode. In the proposed design, although the circuit area does not increase significantly, a fourfold increase in the throughput of the CDMA network is seen. Using the method proposed in this study, it will be possible to increase the capacity further.